Al Qaeda, Islamists and Terrorism in Southeast Asia: A Lesson from the Past - Sahrasad, Herdi; Syukur, Yanuardi; Tabrani, Dedy; Rifai Hasan, Pipip A.; Al Chaidar, Al Chaidar; Mulky, Mohamad Asrori (Jurnal Theologia, 2024)
This article aims to explore the involvement of the Al-Qaeda network in Southeast Asia at the beginning of the 21st century. As an international terrorist organization with sufficient financial and human resources, Al-Qaeda's arrival in Southeast Asia came as a major shock to the local communities affected by it—an injustice caused by the capitalist regimes in the region. The methods used in writing this article are case studies and historical analysis. This article will provide specific examples of Al-Qaeda involvement in several countries in Southeast Asia, such as the case in Poso, Indonesia, where Al-Qaeda members Omar Bandon and Jusuf Galan from Spain provided military training and funding to militant Islamic groups in Malaysia. This article will also discuss Al-Qaeda's involvement in the Philippines, where they formed cells and networks with the Abu Sayyaf and other extreme Islamic groups. The results of this research show that the entry of the Al-Qaeda network in this area has caused terrorism problems and resulted in quite large losses in the form of property and lives. It is hoped that this article will provide new insights and policy recommendations to strengthen counterterrorism efforts in the future.